ANALISA COST OF ILLNESS AKIBAT PENGGUNAAN NSAIDS DI SEBUAH APOTEK DI KOTA MEDAN, INDONESIA - Hari Ronaldo Tanjung; Azmi Sarriff; Urip Harahap (Jurnal Ilmiah Manuntung, 2015)
Background: A drug therapy problem is any undesirable event experienced by a patient which involves, or is suspected to involve drug therapy and that interferes with achieving the desired goals of therapy. Drug Therapy Problems (DTPs) can lead to ineffective pharmacotherapy and may cause drug-related morbidity and mortality.Objective: The study aimed to estimates the direct medical cost of illness caused by the drug morbidity or mortality related to NSAID utilization in a community pharmacy setting at Medan, Indonesia.Method: Thisstudy used 7 (seven) categories probabilities and costs associated with the therapeutic outcomes to estimate the direct medical cost of illness resulting from morbidity related NSAIDs utilization. Direct non medical costs, indirect costs, and intangible costs related to drug-related-morbidity and mortality were not valued in this cost-of-illness analysis.The duration of the study was from July 2009 to October 2010.Result: The patient that experienced NSAIDs-related morbidity estimated to spend Rp.467.848,- each and Rp.11.696.200,- in total to managing the morbidity. Every Rp.1,- spent on NSAIDs therapy, an additional Rp.1,45,- was estimated to spent in managing morbidity related NSAIDs utilization.Conclusion: This result showed the cost of illnessrelated morbidity of NSAIDs utilization exceeds the cost of the medications themselves